2019
DOI: 10.1039/c9cc03379c
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface clicking of antibody-recruiting polymers to metabolically azide-labeled cancer cells

Abstract: Triggering antibody-mediated innate immune mechanisms to kill cancer cells is an attractive therapeutic avenue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…In this regard, bioorthogonal click reactions are an attractive alternative [9] . Moreover, the ease by which azides can be introduced onto a cell surface through metabolic labeling with azido sugars allows for introducing a high density of synthetic low molecular weight cell surface receptors with a reported minimal influence on the cellular functionality [10–12] . Azides immediately prompt the combination with strained cycloalkynes as complimentary reaction partners to form a stable triazole bond through the efficient and highly bioorthogonal strain‐promoted azide‐alkyne cycloaddition (SPAAC) reaction [10] .…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, bioorthogonal click reactions are an attractive alternative [9] . Moreover, the ease by which azides can be introduced onto a cell surface through metabolic labeling with azido sugars allows for introducing a high density of synthetic low molecular weight cell surface receptors with a reported minimal influence on the cellular functionality [10–12] . Azides immediately prompt the combination with strained cycloalkynes as complimentary reaction partners to form a stable triazole bond through the efficient and highly bioorthogonal strain‐promoted azide‐alkyne cycloaddition (SPAAC) reaction [10] .…”
Section: Methodsmentioning
confidence: 99%
“…In vitro analysis showed that only polymers containing both DBCO and DNP were capable to recruit antibodies to an azide‐labeled cancer cell surface in 2D and 3D cell cultures (Figure 8). [65] It is also interesting to note that very recently the Rullo group has reported on antibody recruiting molecules that were able to covalently conjugate to endogenous antibodies through proximity driven ligation [44] which could also open up interesting avenues when translated to macromolecular antibody recruiting entities.…”
Section: Multivalent Antibody‐recruiting Macromoleculesmentioning
confidence: 99%
“…The introduction of bio‐orthogonal azide groups using metabolic glycan labeling has also been used to engineer live cells, through introduction of Ac 4 ManNAz, with antibody‐recruiting polymers (ARPs). [ 75 ] For this purpose, pentafluorophenyl acrylate (PFPA) polymers functionalized with an octyl alkyne were introduced in Jurkat cells and used to immobilize anti‐2,4‐dinitrophenyl (DNP) antibodies on the cell surface (Figure 4C,D). [ 76 ] This concept was further extended to mouse 4T1 spheroids, demonstrating good penetration into the azide‐labeled spheroids and binding to the surface of individual cells.…”
Section: Covalent Conjugation Using Bio‐orthogonal Chemistrymentioning
confidence: 99%